Morpho-Mineralogical and Bio-Geochemical Description of Cave Manganese Stromatolite-Like Patinas (Grotta del Cervo, Central Italy) and Hints on Their Paleohydrological-Driven Genesis - Bernardini, Simone; Bellatreccia, Fabio; Columbu, Andrea; Vaccarelli, Ilaria; Pellegrini, Marika; Jurado, Valme; Del Gallo, Maddalena; Saiz-Jimenez, Cesareo; Sodo, Armida; Millo, Christian; Jovane, Luigi; De Waele, Jo (Frontiers in Earth Science, 2021)
Caves are dark subsurface environments with relatively constant temperatures that allow the study of bio-mineralization processes and paleoenvironmental or climate changes in optimal conditions. In the extreme and oligotrophic cave environment, manganese patinas having stromatolite-like features are uncommon. Here we provide the first detailed mineralogical, geochemical, and microbiological investigation of fine-grained and poorly crystalline MnFe stromatolite-like wall patinas formed in a deep-cave environment in Italy. These mineralizations, about 3 mm thick, consist of an alternation of Mn-layers and Fe-lenses. We show that the microbial communities' composition is dominated by Mn-oxidizing bacteria, such as Bacillus, Flavobacterium, and Pseudomonas. Our multidisciplinary investigation, integrating data from different analytical techniques (i.e., optical microscopy, SEM-EDS, μXRF, XRPD, FT-IR, Raman spectroscopy, and DNA sequencing), revealed peculiar chemical, mineralogical, and biological features: 1) A cyclical oscillation of Mn and Fe along the growth of the patinas. We propose that this oscillation represents the shift between oxic and suboxic conditions related to different phases occurring during paleo-flood events; 2) A typical spatial distribution of mineralogy and oxidation state of Mn, bacterial imprints, detrital content, and stromatolite-like morphologies along the Mn-layers. We propose that this distribution is controlled by the local hydraulic regime of the paleo-floods, which, in turn, is directly related to the morphology of the wall surface. Under less turbulent conditions, the combination of clay mineral catalysis and biological oxidation produced vernadite, a poor-crystalline phyllomanganate with a low average oxidation state of Mn, and branched columnar stromatolite-like morphologies. On the other hand, under more turbulent conditions, the sedimentation of clay minerals and microbial communities' development are both inhibited. In this local environment, a lower oxidation rate of Mn2+ favored the formation of todorokite and/or ranciéite, two compounds with a high average oxidation state of Mn, and flat-laminated or columnar stromatolite-like morphologies.